2011
DOI: 10.4103/0019-5413.80332
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant combined ozone therapy for extensive wound over tibia

Abstract: Disinfectant and antibacterial properties of ozone are utilized in the treatment of nonhealing or ischemic wounds. We present here a case of 59 years old woman with compartment syndrome following surgical treatment of stress fracture of proximal tibia with extensively infected wound and exposed tibia to about 4/5 of its extent. The knee joint was also infected with active pus draining from a medial wound. At presentation the patient had already taken treatment for 15 days in the form of repeated wound debridem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Topical ozone therapy was continued for five days to improve knee infection. After 20 months of follow-up, the bone and soft tissues showed complete recovery, and the patient was able to walk (25 (31) showed that ozone therapy is effective in bone healing in animal models. In an experimental study from Turkey, the researchers evaluated the adjunctive therapeutic effects of hyperbaric oxygen and ozonized oxygen in 48 male Sprague-Dawley rats.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 97%
See 1 more Smart Citation
“…Topical ozone therapy was continued for five days to improve knee infection. After 20 months of follow-up, the bone and soft tissues showed complete recovery, and the patient was able to walk (25 (31) showed that ozone therapy is effective in bone healing in animal models. In an experimental study from Turkey, the researchers evaluated the adjunctive therapeutic effects of hyperbaric oxygen and ozonized oxygen in 48 male Sprague-Dawley rats.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 97%
“…In the past three decades, millions of people have benefited from the therapeutic properties of ozone, while no complications of acute and chronic toxicity have been observed. Ozone appears to have positive effects on the treatment of infections, especially abscesses and sites antibiotics cannot influence (25,26). However, effectiveness of this intervention, as an adjuvant treatment for chronic osteomyelitis, has not been studied adequately, and further investigations are required.…”
Section: Introductionmentioning
confidence: 99%
“…In Russia and all around the world ozone is primary used in wound treatment as an antibacterial agent [1,6,11,12]. Its high oxidative potential is causing hyperactivation of lipid peroxidation initiates the destructive processes in the cell walls of wound bacterial pathogens [1,8,11].…”
Section: Discussionmentioning
confidence: 99%
“…Now there are a two ways of local ozone therapy of different wound. First method includes wound processing with gaseous ozone-oxygen mixtures [11][12][13]. Second technology is based on wound irrigation with ozonized saline or distilled water [1,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…It has been noticed that oxygen-ozone therapy increases the collagen contents of the wounds and upregulates levels of VEGF, TGF- β , and PDGF in wound exudates [ 27 , 28 ]. Some studies have showed that the treatment with oxygen-ozone is an adjuvant to the conventional modality for treatment of extensive orthopaedic wounds [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%